Dekarbonisasi Industri Sebagai Strategi Peningkatan Investasi di Kawasan Industri Maluk Kabupaten Sumbawa Barat - Heriyanto, Heriyanto; Dianto, Dianto; Bahtiar, Syamsul (STAI Darul Kamal NW Kembang Kerang, 2025)
West Sumbawa, which has been designated as an industrial area for the management and refining of copper commodities, is required to increase the investment value other than the target of 21 trillion rupiah. In addition, industrial areas are required to contribute to reducing carbon emissions considering that the industrial sector is the largest contributor to carbon production, thus having an impact on climate change. The aim of this research is to analyze strategies for increasing investment in the West Sumbawa Regency Industrial Area. The research method used in this research is a qualitative research method. The results of this research conclude that 1) the management of the West Sumbawa industrial area is carried out by developing derivative industries from the main industry 2) there are multiple effects from the industrial area such as increasing employment, agricultural production, tourism and other sectors. The findings of this research are decarbonization of industrial areas as a strategy to increase investment amidst demands for industrial areas that require low carbon emissions by changing the status of the West Sumbawa industrial area to a green industrial area.